Effects of countermovement depth on kinematic and kinetic patterns of maximum vertical jumps - Mandic. R.; Jakovljevic, S.; Jaric, S. (Journal of Electromyography and Kinesiology, 2015)
Although maximum height (Hmax), muscle force (F), and power output (P), have been routinely obtained from maximum vertical jumps for various purposes, a possible role of the countermovement depth (Hcmd) on the same variables remains largely unexplored. Here we hypothesized that (1) the optimum Hcmd for maximizing Hmax exists, while (2) an increase in Hcmd would be associated with a decrease in both F and P. Professional male basketball players (N = 11) preformed maximum countermovement jumps with and without arm swing while varying Hcmd ± 25 cm from its preferred value. Although regression models revealed a presence of optimum Hcmd for maximizing Hmax, Hmax revealed only small changes within a wide range of Hcmd. The preferred Hcmd was markedly below its optimum value (p < .05). However, both F and P sharply decreased with Hcmd, while F also revealed a minimum for Hcmd close to its highest values. Therefore, we conclude that although the optimum Hcmd should exists, the magnitude of its effect on Hmax should be only minimal within a typical Hcmd range. Conversely, F and P of leg muscles assessed through maximum vertical jumps should be taken with caution since both of them could be markedly confounded by Hcmd.